Profile of an occupation - forest manager - Schambeck, Arne [Verfasser] (My University, 2020)
"The consequences of climate change are exerting a major influence on vegetation and are changing the face of our woods and forests. All forest tree species have suffered as a result of the extremes of weather experienced over recent years. Instances of damage caused by heat, storms and pests such as the bark beetle are increasing. At the same time, our awareness of woodland as a place of recreation is growing. This draws attention to the occupational profile of forest manager, a field in which requirements are becoming ever more extensive and complex." (author's abstract; BIBB-Doku)
Keywords: S 6.1.1 Land-, Tier-, Forstwirtschaft und Gartenbau; Forstwirt; Berufsbild; Berufsbeschreibung